Peningkatan Keterampilan Membaca Permulaan Dengan Menggunakan Media Kartu Kata Pada Kelas II SD Negeri 012 Rambah Samo - Firnia, Gali (Science and Education Journal (SICEDU), 2024)
This research was motivated by the low initial reading skills of class II students at SD Negeri 012 Rambah Samo. One solution to overcome this problem is to use word card media. The aim of this research is to improve the reading skills of class I students on the theme Myself by using word cards as media. This research method is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, reflection, and research time carried out from July to September. The subjects of this research were 21 class I students. Collection techniques include documentation, observation and tests. The results of this research concluded that students' initial reading skills with the theme Myself in cycle I were classified as poor with a percentage of student completeness with an average score of 61%. Meanwhile in cycle II there was a good improvement, namely student completion was 85%. Thus it can be concluded that using word card media can improve the initial reading skills of class II students at SD Negeri 012 Rambah Samo.